QUICK RATIO, DEBT TO ASSET RATIO, AND RETURN ON ASSETS DETERMINING FACTORS ON: FIRM VALUE (PBV) - Mohamad Yudiansyah Pratama; Hais Dama; Idham Masri Ishak (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of Quick Ratio (QR), Debt to Asset Ratio (DAR), and Return on Assets (ROA) on firm value as measured by Price to Book Value (PBV) in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The consumer non-cyclical sector was selected because it consists of companies producing essential goods with relatively stable demand, making it an important sector in the national economy. This research employed a quantitative approach using secondary data obtained from the annual financial statements of companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, resulting in 196 observations. Data analysis was conducted using multiple linear regression analysis with SPSS software, preceded by classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that partially, Quick Ratio has no significant effect on firm value, indicating that short-term liquidity is not the main consideration for investors in assessing company value. Debt to Asset Ratio also has no significant effect on firm value, meaning that the level of debt dependence does not directly determine market valuation. Meanwhile, Return on Assets has a positive and significant effect on firm value, indicating that profitability is the main factor influencing investor confidence and market value. Simultaneously, Quick Ratio, Debt to Asset Ratio, and Return on Assets have a significant effect on firm value. The coefficient of determination (R²) value of 0.510 indicates that 51.0% of firm value variation can be explained by the three independent variables, while the remaining 49.0% is explained by other factors outside this study.